(untitled) (Per Musi, 2023)
This paper identifies performance elements characteristic of the style of drummer Esdra “Neném” Ferreira. For this purpose, we analyzed the tracks Katendê and Xangô from the CD, Suite para os Orixás, which is the result of a partnership between Neném and Mauro Rodrigues. We showed how certain rhythms and melodies, based on candomblé traditions, were presented by Neném to Mauro and then how they were adapted in the composition of the suite and in the performance of drums and percussion. Finally, by transcribing and analyzing several excerpts of the drums in the two tracks, it was possible to point out some characteristics of Neném’s style, such as the influence of the musical language of candomblé, his constant interaction with the musical material around him, his mastery over odd meters, and his ability to use syncopations, upbeats, and cross rhythms without losing the sense of the groove.